Prevalence of HLA‐B*57:01 allele in Argentinean HIV‐1 infected patients. Issue 1 (29th April 2015) - Moragas, M.; Belloso, W. H.; Baquedano, M. S.; Gutierrez, M. I.; Bissio, E.; Larriba, J. M.; Fay, F.; Aulicino, P.; Gurevich, J. M.; Yaunguzian, M. F.; Maldonado, A. C.; Falistocco, C.; et al.
Abstract Hypersensitivity reaction to abacavir (ABC hypersensitivity syndrome, AHS) is strongly associated with the presence of the HLA‐B*57:01 allele. This study was designed to estimate the prevalence of HLA‐B*57:01 allele in Argentinean HIV‐1 infected patients. We analyzed the presence of HLA‐B*57:01 allele in 1646 HIV‐1 infected patients from different regions of Argentina. This allele was detected in 81 patients; most of them corresponded to patients living in the central region of the country. The prevalence of HLA‐B*57:01 was 4.9%, similar to other Caucasian populations and higher than other data reported for South American populations. This strongly supports screening for the presence of HLA‐B*57:01 in abacavir treatment of HIV‐1 in our country.